2009
DOI: 10.1128/jvi.01968-08
|View full text |Cite
|
Sign up to set email alerts
|

The Human Immunodeficiency Virus Type 1 Nonnucleoside Reverse Transcriptase Inhibitor Resistance Mutation I132M Confers Hypersensitivity to Nucleoside Analogs

Abstract: We previously identified a rare mutation in human immunodeficiency virus type 1 (HIV-1) reverse transcriptase (RT), I132M, which confers high-level resistance to the nonnucleoside RT inhibitors (NNRTIs) nevirapine and delavirdine. In this study, we have further characterized the role of this mutation in viral replication capacity and in resistance to other RT inhibitors. Surprisingly, our data show that I132M confers marked hypersusceptibility to the nucleoside analogs lamivudine (3TC) and tenofovir at both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…The mutations introduced into the recombinant HIV-1 RT did not interfere with either heterodimer formation or enzyme purification. Consistently with previously published data, the E138K mutation did not have an effect on RT dimerization (1,25).…”
Section: Resultssupporting
confidence: 81%
“…The mutations introduced into the recombinant HIV-1 RT did not interfere with either heterodimer formation or enzyme purification. Consistently with previously published data, the E138K mutation did not have an effect on RT dimerization (1,25).…”
Section: Resultssupporting
confidence: 81%
“…Of note, we previously reported that an I132M substitution in the ␤7-␤8 loop (that contains residue E138) of the p51 subunit of HIV-1 RT conferred nevirapine resistance but 3TC hypersusceptibility (8). Taken together, these studies suggest that residues in the ␤7-␤8 loop of HIV-1 RT can influence nucleotide selectivity.…”
mentioning
confidence: 67%
“…Amino acid residue E138 in HIV-1 RT is part of the ␤7-␤8 loop in the p51 subunit, located at the p66/p51 interface, which is a key structural element for RT dimerization, that involves the floor of the NNRTI binding pocket (14,31,32). It was previously shown that E138K did not interfere with either heterodimer formation or enzyme purification (2,29,47). Recombinant WT heterodimeric (p66/p51) RTs and RT enzymes containing each of the E138K, Y181C, and E138K/Y181C substitutions were purified to Ͼ95% homogeneity as demonstrated by Coomassie blue staining of SDS-PAGE gels (Fig.…”
Section: Resultsmentioning
confidence: 99%